Thermal field-flow fractionation (Thermal FFF) and asymmetrical flow field-flow fractionation (AF4) as new tools for the analysis of block copolymers and their respective homopolymers - Ngaza, Nyashadzashe (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.